ANALISIS MANAJEMEN KOMUNIKASI PEMASARAN RADIO METTA SOLO FM DALAM MENINGKATKAN JUMLAH IKLAN - Saputri, Niken Dian; H, Nurnawati Hindra; Astuti I, Andri (Solidaritas, 2024)
Radio has an important role in the process of conveying information through broadcast programs such as music programs, news and advertisements. In the current era of globalization, radio managers must try to ensure that radio continues to exist so that it is not eliminated by the development of globalization. Radio Metta FM was originally a family radio with listeners of all ages, but now Radio Metta has turned into a lifestyle radio where listeners range from 10 to 50 years old. These radio changes result in programs also undergoing changes, therefore marketing management is needed to sell new programs on Metta FM so that there are still advertisements on the radio. This research aims to determine the communication management of Radio Metta Solo FM in increasing the number of advertisements. This type of research is qualitative research using the SOSTAC analysis method by Chaffey and Smith. Data sources consist of primary data, namely interviews and observations, as well as secondary data, namely documentation. The research results show that Radio Metta Solo FM's marketing communications management in increasing the number of advertisements is quite good, as evidenced by a significant increase in the number of advertisements.